Juridical Review of Consumers' Legal Protection Relating to Personal Information Registered with Virtual Wallet Payment Services - Cucuk Endratno; Kumba Digdowiseiso; Feby Kartika Ismawati (Budapest International Research and Critics University, 2022)
The rise of online shopping has given rise to the most recent legal cases, particularly in the area of consumer protection law. The legal protection of online purchasers' personal information is one of the most obvious concerns that need to be addressed. This research aims to identify by legal means the legal protection system linked to individual information registered with virtual wallet payment services and to identify by legal means the legal reinsurance for customers in the event that the legal protection system linked to individual information in the virtual wallet payment service is compromised. The research procedure is normative, observing all applicable laws and regulations pertaining to the monitored legal rumors. Arrangements for the Protection of Individual Information have been included in certain laws and regulations pertaining to Individual Information, but this is not sufficient because the laws and regulations lack a real form of liability for the Electronic System Executor. Until then, the House of Representatives and the rulers are obligated to enact more organized and precise regulations regarding the Protection of Individual Information in their capacity as institutions that create such regulations.